Behaviour of concrete columns with drilled holes - Son, K. S.; Pilakoutas, Kypros; Neocleous, Kyriacos (My University, 2006)
Holes drilled out to install additional services or equipment, such as for ducts through columns, beams or walls, can lead to loss of strength and possible structural failure. Until now little work has been done on holes in columns and, hence, the present study aims to examine the amount of strength lost owing to the presence of holes in columns. The reported experimental work deals with different parameters such as the number and dimensions of the holes and their relative position. It is shown that, for large diameter holes, a section capacity loss of up to 50% is possible. © 2006 Thomas Telford Ltd.
Keywords: Concrete slabs; Concretes; Composite dowels